Stability Indicating Method Development and Validation by Analytical Quality by Design Approach Using UV-Spectrophotometer for Alfuzosin Hydrochloride and Tadalafil in Bulk and Marketed Formulation - Gaonkar, Shalaka G; Dinnimath, Basavaraj Mrutyunjay (Indian Journal of Pharmaceutical Education and Research, 2026)
Introduction: The combination of Alfuzosin and Tadalafil is used to treat both erectile dysfunction and lower urinary tract symptoms. The purpose of this work is to develop and evaluate a UV-spectrophotometric method for simultaneously estimating Alfuzosin hydrochloride and Tadalafil in bulk and marketed formulation, using a Analytical Quality by Design methodology to assure robustness and reliability. Objectives: The current work aims to develop a simple, precise and cost-effective UV-spectrophotometric technique for Alfuzosin Hydrochloride (ALF) and Tadalafil (TAD) and validating in accordance with ICH Q2 (R1) standards by applying Central Composite Design to achieve optimized conditions. Materials and Methods: The UV-spectrophotometric method as a part of green chromatographic approach which was established using 20% methanol as a solvent and both the drugs had maximum absorption at 272 nm (isobestic point). Design Expert software was used to create Design space. The new technique was validated using metrics such as specificity, linearity, precision, robustness, accuracy and ruggedness in accordance with ICH guidelines. Stress degradation experiments were carried out under various conditions, including acidic, basic, oxidative, thermal and photolytic degradation. Results: The technique was found to be linear across concentrations of 4-20 μg/mL, with a correlation value of 0.999. The newly devised approach was found to be specific, linear, precise, rugged and reproducible for estimating ALF and TAD, with %RSD values <2%. Forced degradation study outputs were under acceptable limits of <20%. Conclusion: The AQbD-driven approach develops a highly effective analytical procedure for the simultaneous identification of ALF and TAD without interference. This method provides a robust, efficient and cost-effective approach for routine analysis in quality control analysis.
Keywords: Alfuzosin hydrochloride; Tadalafil; UV-spectrophotometric; ICH guidelines; AQbD.